Counting - Law, Karina; Crawford, Andy (London Franklin Watts, 2009)
First non-fiction books introducing basic skills and concepts in a fun and engaging way. Simple questions encourage young children, from preschool age to early primary, to talk about their ideas and experiences. This title shows them how to count using examples from everyday life
Arithmitic notions
1
Keywords: Arithmetic; Counting -- Pictorial works -- Juvenile literature; Counting